2013
DOI: 10.1681/asn.2012080786
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of the Human Kidney to Isolated Controlled Ischemia

Abstract: Tolerance of the human kidney to ischemia is controversial. Here, we prospectively studied the renal response to clamp ischemia and reperfusion in humans, including changes in putative biomarkers of AKI. We performed renal biopsies before, during, and after surgically induced renal clamp ischemia in 40 patients undergoing partial nephrectomy. Ischemia duration was .30 minutes in 82.5% of patients. There was a mild, transient increase in serum creatinine, but serum cystatin C remained stable. Renal functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 44 publications
7
155
1
6
Order By: Relevance
“…Temporary ischemic changes in mitochondria were evident by electron microscopy with minor tubular injury that began to recover after reflow [40]. These data are consistent with our observations that major tissue hypoxia in the human kidney after 24 h may not result in sustained tissue injury, unlike that observed in experimental models.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 90%
See 1 more Smart Citation
“…Temporary ischemic changes in mitochondria were evident by electron microscopy with minor tubular injury that began to recover after reflow [40]. These data are consistent with our observations that major tissue hypoxia in the human kidney after 24 h may not result in sustained tissue injury, unlike that observed in experimental models.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 90%
“…Remarkably, a recent study of human subjects with total renal artery clamp occlusion for periods between 30 and 60 min during surgery reported minimal kidney injury as determined by levels of creatinine, plasma biomarkers or tissue biopsy [40]. Temporary ischemic changes in mitochondria were evident by electron microscopy with minor tubular injury that began to recover after reflow [40].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 97%
“…However, studies in large mammals, including humans, suggest that global renal hypoperfusion cannot be invoked as the sole etiology of AKI. [2][3][4][5] The causative contribution of renal blood flow (RBF) to kidney dysfunction is particularly puzzling in sepsis, and there is widespread disagreement as to whether RBF is reduced, normal, or even increased. 2,3,[6][7][8] In the few large animal and clinical studies, the patterns of RBF in AKI and its relation with systemic hemodynamics are highly variable.…”
Section: Total Renal Blood Flow In Akimentioning
confidence: 99%
“…The results demonstrated that differential block methods and block time durations were not associated with acute renal function damage, and there were no significant correlations between block time and postoperative renal function. In addition, this study reported surprisingly that the human kidney can tolerate an ischemia time as long as 30 to 60 min [13]. However, all patients in the study had a normal, contralateral kidney.…”
Section: Discussionmentioning
confidence: 70%